2003
DOI: 10.1242/jcs.00627
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of eosinophil membrane depolarization during NADPH oxidase activation

Abstract: (+44.4±1.4 mV) increased depolarization compared with PMA alone. Additionally, the protein kinase C (PKC) δ-selective blocker, rottlerin, inhibited PMA-stimulated depolarization, indicating that PKCδ was involved in regulating depolarization associated with eosinophil NADPH oxidase activity. Thus, the membrane depolarization that is associated with NADPH oxidase activation in eosinophils is sufficient to produce marked proton channel activation under physiological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…We showed that the characteristic V m depolarization in the bud at 6 hpa mechanistically mimics the well-known NADPH oxidasedriven depolarization in immune cells during an oxidative burst (Bankers-Fulbright et al, 2003). This makes it attractive to speculate that V m depolarization is a by-product of ROS production, which is reinforced by the non-requirement of V m depolarization for regeneration.…”
Section: Homeostatic (From 48 Hpa)mentioning
confidence: 54%
“…We showed that the characteristic V m depolarization in the bud at 6 hpa mechanistically mimics the well-known NADPH oxidasedriven depolarization in immune cells during an oxidative burst (Bankers-Fulbright et al, 2003). This makes it attractive to speculate that V m depolarization is a by-product of ROS production, which is reinforced by the non-requirement of V m depolarization for regeneration.…”
Section: Homeostatic (From 48 Hpa)mentioning
confidence: 54%
“…The extrusion of electrons across the membrane to generate superoxide develops a potential across the membrane. The depolarization will impose bioenergetic limits on the enzyme activity and thus curtail ROS generation if there is no route for charge compensation (Henderson et al, 1987;Bankers-Fulbright et al, 2003;Rada et al, 2005). Although several ion channels have been ascribed this role in other cell types, an issue that has proven highly controversial (DeCoursey, 2003;Ahluwalia et al, 2004), it is evident that any functional conductance in the membrane during NOX2 activity will inevitably contribute to setting the membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore propose a novel feedforward mechanism, whereby activation of the oxidase and resultant ROS production promotes a redox-controlled structural transition of CLIC1 and promotes its insertion into the membrane where it carries an anion conductance. The increase in CLIC1-mediated chloride conductance then facilitates ROS generation by NOX2 by providing a conductance that offsets the membrane potential change generated by NOX2 activity and permitting sustained ROS generation by the oxidase (Henderson et al, 1987;Bankers-Fulbright et al, 2003;Rada et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This electron movement can be recorded directly as an electrical current (10,5). Because the electron transport is not obligatorily coupled to a compensatory charge movement, it produces a separation of charge that leads to sustained depolarization of the membrane (62) well beyond 0 mV in intact granulocytes (63)(64)(65)(66). If this charge movement is not compensated, extreme depolarization results (67,61) that by itself directly opposes electron flux across the membrane (25).…”
Section: Introductionmentioning
confidence: 99%